Who Dominates the Discourses of the Past? Gender, Occupational Affiliation, and Multivocality in North American Archaeology Publishing. Issue 3 (July 2019) - Fulkerson, Tiffany J.; Tushingham, Shannon
Abstract : Equity and the dissemination of knowledge remain major challenges in science. Peer-reviewed journal publications are generally the most cited, yet certain groups dominate in archaeology. Such uniformity of voice profoundly limits not only who conveys the past but also what parts of the material record are narrated and/or go untold. This study examines multiple participation metrics in archaeology and explores the intersections of gender and occupational affiliation in peer-reviewed (high time cost) and non-peer-reviewed (reduced time cost) journals. We find that although women and compliance archaeologists remain poorly represented in regional and national peer-reviewed journals, they are much more active in unrefereed publications. We review feminist and theoretical explanations for inequities in science and argue that (1) the persistent underrepresentation of women and of compliance professionals in archaeological publishing are structurally linked processes and (2) such trends can be best understood in light of the existing structure of American archaeology and the cost-benefit realities of publishing for people in various sectors of the discipline. We suggest that nonrefereed venues offer a pathway to multivocality and help to address epistemic injustices, and we discuss methods for widening the current narrow demographic of men and academics who persist in dominating discourses. Abstract : La equidad y la difusión del conocimiento siguen siendo grandes desafíos de la ciencia. Las publicaciones de revistas revisadas por pares son generalmente las más citadas, sin embargo, ciertos grupos dominan en arqueología. Esta uniformidad de voz limita profundamente no solo quién transmite el pasado, sino también que partes del registro material se narran y/o no se mencionan. Este estudio examina múltiples métricas de participación en arqueología y explora las intersecciones de género y afiliación ocupacional en revistas revisadas por pares (costo de tiempo alto) y no revisadas por pares (costo de tiempo reducido). Encontramos que aunque las mujeres y arqueólogos por contrato siguen siendo poco representados en revistas arbitradas regionales y nacionales, son mucho más activos en publicaciones no arbitradas. Revisamos explicaciones feministas y teóricas de las inequidades en la ciencia y argumentamos que (1) la representación insuficiente de mujeres y de profesionales por contrato en publicaciones arqueológicas son procesos estructuralmente vinculados y (2) las tendencias se pueden entender mejor a la luz de la estructura existente de la arqueología estadounidense y las realidades de costo-beneficio de la publicación para el público en diversos sectores de la disciplina. Sugerimos que las plataformas no arbitradas ofrezcan un camino hacia la multivocalidad y ayuden a abordar las injusticias epistémicas y discutan métodos para ampliar la estrecha demografía actual de hombres y académicos que persisten en los discursos dominantes.